The Relationship Of Organizational Culture And School Principal Leadership With Decision Making In State High Schools In Balige District - Lubis, Resita; Pakpahan, Betty A.S.; Lubis, Bernard; C.Marbun, Rencan; Gultom, Rogate.A.T. (JUPE : Jurnal Pendidikan Mandala, 2024)
The aims of this research are to 1) analyze the relationship between organizational culture and decision making of school principals in public high schools in Balige District; 2) analyze the relationship between leadership and decision making of school principals in State High Schools in Balige District; and 3) analyze the relationship between organizational culture and leadership, together with the decision making of school principals in State High Schools in Balige District. The method used in this research is quantitative inferential. The population is all teachers in public high schools in Balige District, totaling 100 people and a sample of 50 people was determined using random sampling techniques. Data was collected using a closed questionnaire with 80 items. The results of data analysis show that: 1) the value of tcount > ttable (α=0.05; n-2=48) between organizational culture and decision making is 4.420 > 2.021, thus it is known that there is a relationship between organizational culture and decision making in state high schools throughout -Balige District; 2) the value of tcount > ttable (α=0.05; n-2=48) between school principal leadership and decision making is 3.547 > 2.021, thus it is known that the relationship between principal leadership and decision making in State High Schools throughout Balige District; 3) the value of Fcount > Ftable (k=2;n-2=48) between organizational culture and principal leadership and decision making is 12.706 > 3.23, thus it is known that there is a relationship between organizational culture and principal leadership simultaneously with decision making in public high schools in Balige District, thus Ha is accepted and H0 is rejected.